Influence of Darkness Dry and Darkness Rainfall on Malaysian Expressway for Traffic Characteristics using Greenshield’s Model - Parameswary, Sundara; Mohd Rosli, Hainin; Che Puan, Othman; Kamal Z., Zamli (TextRoad Publication, 2015)
The study is concerned on evaluating traffic performance during darkness time on expressways. The study aimed at comparing influence of dry and rainfall weather condition. In a threshold impact of darkness, traffic flow characteristics on expressway at two different locations in Malaysia were investigated. Based on the investigation, data for travel speed, traffic flow and density were obtained continuously for three weeks at the selected segment of expressway in Slim River and supplemented with dry and rainfall data culled from Projek Lebuhraya Utara Selatan (PLUS). Observation periods for nature light, darkness and artificial light for the selected sites are 24 hours including darkness rainfall and darkness dry weather condition. Results show that density appears to be sensitive to speed, although the scatter decreases at higher speeds during darkness condition. Average speeds in the region of the higher densities region or lowers densities region appears to be a linear relationship and show reasonable agreements with the typical Greenshield’s hypothesis for both darkness dry and darkness rainfall as far as the range of the data allows. Study concluded that comparison between darkness dry and darkness rainfall for Greenshield’s model has no or less significant effect on traffic flow characteristics at the respective sites.